1932
DOI: 10.1017/s0022172400018246
|View full text |Cite
|
Sign up to set email alerts
|

The Utilisation of Citrates and the Fermentation of Cellobiose by Strains ofBacterium ColiIsolated from Human Faeces

Abstract: 1. Of 585 strains of lactose-fermenting aerobes each isolated from faeces of a different person, 501 did not utilise citrate or ferment cellobiose; 20 were citrate negative and cellobiose positive; 27 were cellobiose negative and citrate positive; and 37 were positive to both tests.2. Almost 10 per cent, of the strains isolated were indol negative.3. One culture was methyl-red negative and Voges-Proskauer positive. Two were positive to both tests. The rest were methyl-red positive and Voges-Proskauer negative.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1933
1933
1957
1957

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 16 publications
(1 reference statement)
0
11
0
Order By: Relevance
“…They ferment cellobiose, but fail to utilize citrate. Similar cultures have been isolated from soil by Koser (1926); from human feces by Skinner and Brudnoy (1932), 360 RALPH P. TITTSLER AND LESLIE A. SANDHOLZER and from water by Poe (1934). These strains are similar to typical members of the Escherichia genus.…”
Section: Discussionmentioning
confidence: 59%
“…They ferment cellobiose, but fail to utilize citrate. Similar cultures have been isolated from soil by Koser (1926); from human feces by Skinner and Brudnoy (1932), 360 RALPH P. TITTSLER AND LESLIE A. SANDHOLZER and from water by Poe (1934). These strains are similar to typical members of the Escherichia genus.…”
Section: Discussionmentioning
confidence: 59%
“…Skinner & Brudnoy (1932) isolated nearly 11 % of citrate utilizers among 585 strains of lactose-fermenting bacilli from human faeces, Cruickshank (1930) found that ninety-eight out of 135 samples of human stools yielded aerogenes and Gray (1932) isolated this organism from thirty-seven of forty similar specimens by preliminary incubation in citrate medium followed by plating on MacConkey agar. Hill and his co-workers (1929) isolated more than 39 % aerogenes among 200 strains of Gram-negative bacilli from genito-urinary infections and Burke-Gaffney (1933) found that 8% of 500 faecal and 52 % of 1000 urinary strains were aerogenes.…”
Section: Discussionmentioning
confidence: 99%
“…The high incidence of Aerobacter was unexpected, Skinner and Brudnoy (1932) found only 3 out of 585 cultures of coliforms isolated at random from feces of 585 persons to be Aerobacter. Others usually have not found as many A erobacter as we did in the present study.…”
Section: Taken Miaterials An-i) Miethodsmentioning
confidence: 99%
“…Escherichia coli as delimited in Bergey's Mllanual of Determinative Bacteriology (Breed et al, 1948) and "fecal coliforms" are not synonymous. Skinner and Brudnoy (1932) have shown that more than 10 per cent of the Escherichia strains isolated from human feces were described in Bergey's Mllanual of Determinative Bacteriology (Breed et al, 1948) as E. freundii. A medium may be inhibitory to the organisms Inot desired, but such an agent may still inhibit many or most of the cells of the desired species.…”
mentioning
confidence: 99%